The Tax Benefits: Myths and truths - Pacheco, Cláudio Gonçalves (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
Abstract: Taking into account that the repeated practice of using tax benefits as an instrument of socioeconomic policy is recurrent in the public administrations of Brazilian governments, this study aimed to verify the myths that surround them. What is true or what is a myth behind the speeches that legitimize them, as they are always apologetic and equipped with rhetoric that has long been worn out, such as promoting production and invention, promoting job creation, developing public infrastructure, maintaining and improves public health, stimulates housing construction, protects the environment, enables the optimization of production chains, reduces social and regional inequalities, etc., in short, catalyzes and materializes economic growth and fundamental social transformations. To this extent, the objective is to support modern theories that help in understanding the truth or falsehood of the propositions discussed above, as well as verifying the practical repercussions of tax expenditures, above all, on their much-vaunted socioeconomic return and the prospects for compromising the fair allocation of tax revenues. Pay attention to the possible erosion of the ICMS tax base with the transfer of tax resources to the private sector and present possible suggestions to combat this distortion.